More Than a Methanotroph: A Broader Substrate Spectrum for Methylacidiphilum fumariolicum SolV - Picone, Nunzia; Mohammadi, Sepehr S.; Waajen, Annemiek C.; van Alen, Theo A.; Jetten, Mike S. M.; Pol, Arjan; Op den Camp, Huub J. M. (Frontiers in Microbiology, 2020)
Volcanic areas emit a number of gases including methane and other short chain alkanes, that may serve as energy source for the prevailing microorganisms. The verrucomicrobial methanotroph Methylacidiphilum fumariolicum SolV was isolated from a volcanic mud pot, and is able to grow under thermoacidophilic conditions on different gaseous substrates. Its genome contains three operons encoding a particulate methane monooxygenase (pMMO), the enzyme that converts methane to methanol. The expression of two of these pmo operons is subjected to oxygen-dependent regulation, whereas the expression of the third copy (pmoCAB3) has, so far, never been reported. In this study we investigated the ability of strain SolV to utilize short-chain alkanes and monitored the expression of the pmo operons under different conditions. In batch cultures and in carbon-limited continuous cultures, strain SolV was able to oxidize and grow on C1-C3 compounds. Oxidation of ethane did occur simultaneously with methane, while propane consumption only started once methane and ethane became limited. Butane oxidation was not observed. Transcriptome data showed that pmoCAB1 and pmoCAB3 were induced in the absence of methane and the expression of pmoCAB3 increased upon propane addition. Together the results of our study unprecedently show that a pMMO-containing methanotroph is able to co-metabolize other gaseous hydrocarbons, beside methane. Moreover, it expands the substrate spectrum of verrucomicrobial methanotrophs, supporting their high metabolic flexibility and adaptation to the harsh and dynamic conditions in volcanic ecosystems.